Formation of Monofluorinated Radical Cofactor in Galactose Oxidase through Copper-Mediated C−F Bond Scission - Li, Jiasong (J Am Chem Soc, 2020)
Galactose oxidase (GAO) contains a Cu(II)-ligand radical cofactor. The cofactor, which is autocatalytically generated through the oxidation of the copper, consists of a cysteine-tyrosine radical (Cys-Tyr(•)) as a copper ligand. The formation of the crosslinked thioether bond is accompanied by a C-H bond scission on Tyr272 with few details known thus far. Here, we report the genetic incorporation of 3,5-dichlorotyrosine (Cl(2)-Tyr) and 3,5-diflurotyrosine (F(2)-Tyr) to replace Tyr272 in the GAO(V) previously optimized for expression through directed evolution. The proteins with an unnatural tyrosine residue are catalytically competent. We determined the high-resolution crystal structures of the GAO(V), Cl(2)-Tyr272, and F(2)-Tyr272 incorporated variants at 1.48, 1.23, and 1.80 Å resolution, respectively. The structural data showed only one halogen remained in the cofactor, indicating that an oxidative carbon-chlorine/fluorine bond scission has occurred during the autocatalytic process of cofactor biogenesis. Using hydroxyurea as a radical scavenger, the spin-coupled hidden Cu(II) was observed by EPR spectroscopy. Thus, the structurally defined catalytic center with genetic unnatural tyrosine substitution is in the radical containing form as in the wild-type, i.e., Cu(II)-(Cl-Tyr(•)-Cys) or Cu(II)-(F-Tyr(•)-Cys). These findings illustrate a previously unobserved C−F/C-Cl bond cleavage in biology mediated by a mononuclear copper center.